2013
DOI: 10.1016/j.molonc.2013.07.008
|View full text |Cite
|
Sign up to set email alerts
|

SPARCL1 suppresses metastasis in prostate cancer

Abstract: Purpose Metastasis, the main cause of death from cancer, remains poorly understood at the molecular level. Experimental design Based on a pattern of reduced expression in human prostate cancer tissues and tumor cell lines, a candidate suppressor gene (SPARCL1) was identified. We used in vitro approaches to determine whether overexpression of SPARCL1 affects cell growth, migration, and invasiveness. We then employed xenograft mouse models to analyze the impact of SPARCL1 on prostate cancer cell growth and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 43 publications
(64 reference statements)
5
27
0
Order By: Relevance
“…According to the results of our meta-analysis, the overexpression of SPARCL1 may reduce cancer metastasis (including lymph node and distant metastases) which contributes to survival benefits. Furthermore, some scientists have concluded that SPARCL1 gene plays a suppressor role in tumor metastasis in various cancers [24, 33, 34]. Our results also showed that the expression of SPARCL1 indicated better tumor differentiation (OR=2.21, P =0.000).…”
Section: Discussionsupporting
confidence: 73%
“…According to the results of our meta-analysis, the overexpression of SPARCL1 may reduce cancer metastasis (including lymph node and distant metastases) which contributes to survival benefits. Furthermore, some scientists have concluded that SPARCL1 gene plays a suppressor role in tumor metastasis in various cancers [24, 33, 34]. Our results also showed that the expression of SPARCL1 indicated better tumor differentiation (OR=2.21, P =0.000).…”
Section: Discussionsupporting
confidence: 73%
“…While several functional studies support that SPARCL1 restricts tumor growth and progression (4, 6, 7), the role for SPARCL1 in prostate cancer remains poorly understood. The correlation between SPARCL1 loss and aggressiveness of clinically localized prostate cancer suggests that SPARCL1 may function as a barrier to tumor initiation and progression in the prostate (4).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this, overexpression of SPARCL1 in colon cancer cells suppressed growth of subcutaneous xenografts (6). While SPARCL1 has been shown to inhibit in vitro proliferation of colon cancer (6) and HeLa (8) cells, other studies support that SPARCL1 may not regulate cellular proliferation in the prostate (4, 7). Alternatively, SPARCL1 has been shown in multiple models to inhibit processes integral to both local and metastatic progression such as cancer cell adhesion, migration and invasion (4, 6, 7, 9, 10).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations